Transcriptome Analysis of Interspecific Hybrid between Brassica napus and B. rapa Reveals Heterosis for Oil Rape Improvement - Jinfang Zhang; Guangrong Li; Haojie Li; Xiaobin Pu; Jun Jiang; Liang Chai; Benchuan Zheng; Cheng Cui; Zujun Yang; Yongqing Zhu; Liangcai Jiang (International Journal of Genomics)
The hybrid between Brassica napus and B. rapa displays obvious heterosis in both growth performance and stress tolerances. A comparative transcriptome analysis for B. napus (AnAnCC genome), B. rapa (ArAr genome), and its hybrid F1 (AnArC genome) was carried out to reveal the possible molecular mechanisms of heterosis at the gene expression level. A total of 40,320 nonredundant unigenes were identified using B. rapa (AA genome) and B. oleracea (CC genome) as reference genomes. A total of 6,816 differentially expressed genes (DEGs) were mapped in the A and C genomes with 4,946 DEGs displayed nonadditively by comparing the gene expression patterns among the three samples. The coexistence of nonadditive DEGs including high-parent dominance, low-parent dominance, overdominance, and underdominance was observed in the gene action modes of F1 hybrid, which were potentially related to the heterosis. The coexistence of multiple gene actions in the hybrid was observed and provided a list of candidate genes and pathways for heterosis. The expression bias of transposable element-associated genes was also observed in the hybrid compared to their parents. The present study could be helpful for the better understanding of the determination and regulation of mechanisms of heterosis to aid Brassica improvement.